Periphyton Response Analysis to the Pollution in Seagrass Ecosystem Panjang Island, Banten - Yayuk Sugianti; Barti Setiani Muntalif; Priana Sudjono (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2018)
Increases in coastal pollutants, largely due to human activity on land, have an impact on seagrass ecosystems. The high sedimentation in the waters causes an increase in the concentration of sludge, organic matter, nutrients, and turbidity which reduce the depth that can be reached by sunlight. The condition affects seagrass ecosystems adversely. Changes in water condition can be illustrated by the presence of water organisms. One dominant organism in seagrass ecosystems is periphyton. The existence of periphyton in the waters is determined by physical and chemical conditions of the waters because it has specific limit of tolerance, which causes different community structure. To analyze periphyton response to the changes of environmental quality in seagrass ecosystems, Shannon Winner diversity and Saprobic Indices were measured at Panjang Island, Banten. The results of water quality assessment indicates the status of aquatic seagrass of the island considered as polluted to heavy polluted. It is observed from some physico-chemical parameters that exceeded the standard quality for the life of seagrass ecosystems and marine life. Based on the classification and saprobic coefficient using periphyton biological parameters, the condition of seagrass land ecosystem in the island is classified into β Mesosaprobic to β/α Mesosaprobic phase, which indicates light to medium pollution with pollutants including organic and inorganic materials. Several types of dominant periphyton were discovered during the observations, including Meridion sp, Navicula sp, Nitzschia sp and Synedra sp. This periphyton species belong to Bacillariophyceae class (Family Chrysophyta) that is commonly used to assess the condition of eutrophication and organic pollution on waters.